Designing for the circular economy - Charter, Martin (Routledge, Taylor & Francis Group, 2019)
The circular economy describes a world in which reuse through repair, reconditioning and refurbishment is the prevailing social and economic model. The business opportunities are huge but developing product and service offerings and achieving competitive advantage means rethinking your business model from early creativity and design processes, through marketing and communication to pricing and supply. Designing for the Circular Economy highlights and explores ‘state of the art’ research and industrial practice, highlighting CE as a source of: new business opportunities; radical business change; disruptive innovation; social change; and new consumer attitudes. The thirty-four chapters provide a comprehensive overview of issues related to product circularity from policy through to design and development. Chapters are designed to be easy to digest and include numerous examples. An important feature of the book is the case studies section that covers a diverse range of topics related to CE, business models and design and development in sectors ranging from construction to retail, clothing, technology and manufacturing.Designing for the Circular Economy will inform and educate any companies seeking to move their business models towards these emerging models of sustainability; organizations already working in the circular economy can benchmark their current activities and draw inspiration from new applications and an understanding of the changing social and political context. This book will appeal to both academia and business with an interest in CE issues related to products, innovation and new business models.